2006
DOI: 10.2215/cjn.00790306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prednisone versus No Prednisone as Part of Maintenance Immunosuppression on Long-Term Renal Transplant Function

Abstract: Corticosteroids have been a component of maintenance immunosuppression for renal transplant since the 1960s and have helped to reduce the rate of acute rejection. Corticosteroids, however, have many adverse effects, and with the development of new immunosuppressive medications, many transplant centers have adopted protocols that eliminate or completely avoid the use of corticosteroids. Despite promising short-term results, the impact of corticosteroid elimination on long-term kidney function still is unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…Steroids are a known cause of insulin resistance, and the CNI impair insulin secretion. The tendency for a greater prevalence of diabetes with tacrolimus versus cyclosporine is diminished with steroid-free protocols and with the lower dosages of tacrolimus being used today (25,106,(111)(112)(113)(114). Although higher dosages of steroids clearly lead to more diabetes, Midvedt et al…”
Section: Role Of Immunosuppressive Agentsmentioning
confidence: 99%
“…Steroids are a known cause of insulin resistance, and the CNI impair insulin secretion. The tendency for a greater prevalence of diabetes with tacrolimus versus cyclosporine is diminished with steroid-free protocols and with the lower dosages of tacrolimus being used today (25,106,(111)(112)(113)(114). Although higher dosages of steroids clearly lead to more diabetes, Midvedt et al…”
Section: Role Of Immunosuppressive Agentsmentioning
confidence: 99%
“…The incidence of SIDM reduced from 20% in a study that gave 5-7.5mg/day for maintenance over a five year period 10 to 7% in another study that prescribed 2.5mg/day for two years 11 . The non use of steroids as maintenance agents is however being advocated for, in renal transplant patients because of the associated side effects 10 . There is a need to consider the non use of steroid in combination chemotherapy for haematological disorder if SIDM is reported from other centres and after a controlled trial confirms the finding.…”
Section: Discussionmentioning
confidence: 94%
“…This complication was also observed in patients in the middle age with a predilection for female (though only four patients were seen), which is similar to what was observed in a group of patients treated with steroid for varied respiratory diseases 4 . A common finding in cases of steroid induced diabetes mellitus (SIDM) is that it appears not to be dose related and risk factors are not readily identified even though some studies have alluded to a higher prevalence in people of black ancestry but this is yet to be confirmed 9,10 . The cumulative dose until the diagnosis of DM ranged between 500-1800mg in our group of patients while in the patients who developed SIDM after treatment for respiratory diseases the cumulative dose ranged between 940-23590mg.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the chronic steroid group had higher incidence of hyperlipidemia and post transplantation diabetes compared to the rapid steroid elimination group. 72 A meta-analysis of 6 randomized steroid withdrawal trials, while receiving MMF based immunosuppression showed that the risk of acute rejection episodes after steroid elimination was 2.28 times higher than that observed in patients maintained on steroids, but this did not affect graft survival at medium term follow up. The reduction in total cholesterol level was signifi cant in the steroid withdrawal group.…”
Section: Steroid-sparing Regimensmentioning
confidence: 99%